The literary politics of Mitteleuropa : reconfiguring spatial memory in Austrian and Yugoslav literature after 1945 - Zivkovic, Yvonne (Studies in German literature, linguistics, and culture., 2021)
Shows how postwar writers in Austria and Yugoslavia re-imagined Mitteleuropa as a cultural space between nostalgia and totalitarianism.